Perceived benefit, perceived barrier dan dukungan sosial terhadap perawatan diri pasien setelah operasi Coronary Artery Bypass Graft (CABG) - Mulida Arifiati; Sri Yona; Tuti Herawati (Holistik Jurnal Kesehatan, 2022)
Background: CABG surgery is one of the surgical treatments for CHD and improves the patient's quality of life. However, patients who have undergone CABG remain at risk for ischemic events. Cardiovascular secondary prevention plays an important role to maintain the long-term patency of the graft, slowing the atherosclerotic process. Behavior change is influenced by a person's belief to change and support around him. The beliefs that are considered to have an effect on the pattern of behavior change are perceived benefits and perceived barriers.Purpose: To determine the relationship between perceived benefit, perceived barrier, and social support to patient self-care after CABG surgery.Method: Cross-sectional design, with a sample size of 75 respondents, inclusion criteria: CABG surgery patients more than 6 months, Age more than 30 years.Results: From the analysis, there are four significant relationships with self-care, education p-value of 0.015, perceived benefit p-value of 0.001, perceived barrier with a p-value of 0.004, and social support p-value of 0.000. What is not significant is the age p-value of 0.631 and knowledge p-value of 0.418 Gender p-value of 0.357.Conclusion: There is a significant relationship between perceived benefit, perceived barrier, and social support for patient self-care after CABG surgery.Keywords: Perceived Benefit; Perceived Barriers; Social Support; Self Care; CABG.Pendahuluan: Operasi CABG merupakan salah satu penanganan bedah pada PJK dan meningkatkan kualitas pasien kehidupan baik. Namun pasien yang telah menjalani CABG tetap berisiko untuk kejadian iskemik. Pencegahan sekunder kardiovaskular memainkan peran penting untuk mempertahankan jangka panjang patensi cangkok, memperlambat proses aterosklerotik. Perubahan perilaku dipengaruhi oleh keyakinan seseorang untuk berubah dan dukungan disekitarnya. Keyakinan yang dianggap berpengaruh terhadap pola perubahan perilaku adalah perceived benefit dan perceived barrier.Tujuan: Untuk mengetahui hubungan perceived benefit, perceived barrier dan dukungan sosial terhadap perawatan diri pasien setelah operasi CABG.Metode: Desain cross-secrtional, dengan jumlah sampel 75 responden, kriteria inklusi: Pasien operasi CABG lebih dari 6 bulan, Usia lebih dari 30 tahun.Hasil: Dari analisis terdapat empat hubungan yang bermakna terhadap perawatan diri, didapatkan pendidikan nilai p 0,015, perceived benefit nilai p 0,001, perceived barrier dengan nilai p 0,004 , dan dukungan social nilai p 0,000. Yang tidak bermakna yaitu usia nilai p 0.631dan pengetahuan nilai p 0.418 Jenis kelamin nilai p 0,357.Simpulan: Terdapat hubungan yang bermakna anatara perceived benefit, perceibved barrier, dan dukungan social terhadap perawatan diri pasien setelah operasi CABG.